2003
DOI: 10.1074/jbc.m308996200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Relaxin-3/INSL7 as a Ligand for GPCR142

Abstract: We have recently identified the insulin-like peptide relaxin-3 (aka INSL7) as the endogenous ligand for an orphan G-protein-coupled receptor, GPCR135 (aka somatostatin-and angiotensin-like peptide receptor). Analysis of possible receptors related to GPCR135 revealed a single orphan receptor, GPCR142. Thus, we tested whether GPCR142 could also respond to relaxin-3 or related insulin-like molecules. Surprisingly, GPCR142 was activated by nanomolar concentrations of relaxin-3 but was completely unresponsive to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
273
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(282 citation statements)
references
References 22 publications
(27 reference statements)
4
273
1
4
Order By: Relevance
“…Two additional receptors for relaxin-3 have been identified, known as GPCR135 (RXFP3) and GPCR142 (RXFP4) [27,28]. Neither of these receptors is activated by relaxin or InsL3.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional receptors for relaxin-3 have been identified, known as GPCR135 (RXFP3) and GPCR142 (RXFP4) [27,28]. Neither of these receptors is activated by relaxin or InsL3.…”
Section: Discussionmentioning
confidence: 99%
“…The determinants for H3 relaxin activity on RXFP3 and RXFP4 are probably located in the B-chain alone, since synthetic S-reduced H3 relaxin B-chain is an RXFP3 and RXFP4 agonist (12,13). It has recently been demonstrated that key residues in the H3 relaxin B-chain are responsible for both binding affinity and cAMP-inhibitory activity (14).…”
mentioning
confidence: 99%
“…Thus, GPR100 could potentially be a kinin receptor subtype and BK a GPR100 ligand. However, this theory was questioned when Liu et al (2003) almost simultaneously proposed that insulin-like peptide relaxin 3 is a ligand for GPR100 since it binds to and stimulates GTPgS binding and inhibits AC through this receptor at nanomolar concentrations. Consequently, this led to the question: Is GPR100 a BK or relaxin receptor or both?…”
mentioning
confidence: 99%